English for Tourism : Peningkatan Kemampuan Komunikasi Bahasa Inggris Bagi Anggota Geopark Youth Forum Kabupaten Lebak - Siti Hanna Sumedi; Hikmah Pravitasari (Jejaring Penelitian dan Pengabdian Masyarakat, 2023)
Improving English language communication skills is crucial for members of the Geopark Youth Forum (GYF) in Kabupaten Lebak to face the growing tourism sector. This study aims to conduct a community engagement program entitled